Concerns and priority outcomes for children with advanced cancer and their families in the Middle East: A cross-national qualitative study - Boufkhed, Sabah; Yurduşen, Sema; Alarjeh, Ghadeer; Ahmed, Fahad; Alrjoub, Waleed; Guo, Ping; Alajarmeh, Sawsan; Şengelen, Meltem; Cemaloğlu, Mustafa; Aydın, Burça; Alnassan, Anwar; Al-Awady, Shireen; et al. (Frontiers in Oncology, 2023)
Introduction: Palliative care access is limited in the Middle-East, with few specialist centres and forcibly displaced migrants facing additional struggles to access care. Little is known about the specificities of providing palliative care to children and young people (CYP) with cancer. They are rarely asked directly their concerns and needs, which limits the provision of quality patient-centred care. Our study aims to identify the concerns and needs of CYP with advanced cancer and their families, in Jordan and Turkey. Method: A qualitative cross-national study in Jordan and Turkey with framework analysis was conducted two paediatric cancer centres in Jordan and Turkey. In each country, 25 CYP, 15 caregivers and 12 healthcare professionals participated (N=104). Most caregivers (70%) and healthcare professionals (75%) were women. Results: We identified five areas of concern: (1) Physical pain and other symptoms (e.g. mobility, fatigue); (2) Psychological concerns and needs (e.g. anger, psychological changes); (3) Spirituality, uncertainty over the future and use of “Tawakkul” (e.g. use of religion as a coping mechanism); (4) Negative impact on social life (e.g. social isolation, loss of support); (5) Burden on caregiver and their families (e.g. financial issues, siblings left behind). Psychological concerns were a priority for both CYPs and caregivers (particularly for refugee and displaced families) but often overlooked during routine care. CYP were able to share their own concerns and care priorities. Conclusions: Advanced cancer care must ensure assessment and management of concerns across the concerns identified. Developing child- and family-centred outcomes would ensure monitoring the quality of care. Spirituality had a more important role compared to similar investigation in other regions.